Community perspectives of South African adolescents’ experiences seeking treatment at local HIV clinics and how such clinics may influence engagement in the HIV treatment cascade: A qualitative study - Ritchwood, Tiarney D. (AIDS Care, 2019)
Despite having the largest antiretroviral treatment (ART) program in the world, only 14% of South African adolescents living with HIV (ALWH) are on ART. The purpose of this study was to identify aspects of the clinic environment that either improve or inhibit ALWH’s ability to engage in HIV care. We conducted fifty-nine semi-structured, in-depth interviews with ALWH (n=20; 13-19 years of age), their caregivers (n=19), and local stakeholders (n=20) in Cape Town, South Africa. Data were coded and analyzed using inductive and deductive approaches to content analyses. Codes were grouped into positive and negative aspects of the HIV clinic environment, and into suggestions on how clinic practices could be improved to facilitate ALWH treatment retention and ART adherence. Positive clinic factors included: community co-location; familiarity with clinic staff; and adolescent only/adolescent-friendly clinic spaces. Negative clinic factors included: clinic visit frequency; overcrowding and long wait times; discrimination and stigma; lack of confidentiality; inflexible appointment-scheduling; and staff attitudes. ALWHs’ clinic experiences affect their ability to remain in care and adhere to their treatment regimens. These findings support a call for innovative approaches that improve ALWH’s clinic experiences and support them as they progress along the HIV treatment cascade.